The expert meeting dedicated to the discussion of results of a local open-label multicenter observational study of the efficiency and safety of tofacitinib in patients with active rheumatoid arthritis with the inefficiency of disease-modifying antirheumatic drugs and to the elaboration of recommendations for the use for tofacitinib in the therapy of rheumatoid arthritis (Научно-практическая ревматология, 2016)
The expert meeting dedicated to the discussion of results of a local open-label multicenter observational study of the efficiency and safety of tofacitinib in patients with active rheumatoid arthritis with the inefficiency of disease-modifying antirheumatic drugs and to the elaboration of recommendations for the use for tofacitinib in the therapy of rheumatoid arthritis.